Morphological redescription and DNA barcoding of Linevitshia prima Makarchenko, 1987 (Diptera: Chironomidae: Diamesinae) from Amur River basin (Russian Far East), with notes on systematics of the genus - Makarchenko, Eugenyi A.; Semenchenko, Alexander A. (Zootaxa, 2014)
Additions and corrections to the diagnosis of the genus Linevitshia for male adult, pupa and larva are given, and systematic position of the genus is discussed. Illustrated redescription of adult male and first description of 4th instar larva of L. prima Makarchenko from Amur River basin are provided. Comparison of data based on a new material with those of L. yezoensis Endo showed that the latter name is a junior synonym of L. prima. The species-specificity of L. prima COI sequences is analyzed and the sequences are presented as diagnostic characters—molecular markers of L. prima.